2002
DOI: 10.1016/s0022-5347(05)64270-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Multi-target Fluorescent in Situ Hybridization Assay for Detection of Bladder Cancer

Abstract: Sensitivity of the FISH assay is superior to that of cytology and at least equivalent to the BTA Stat test in detecting recurrent transitional cell carcinoma. Its specificity approaches that of cytology. Further testing of its clinical use is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(82 citation statements)
references
References 16 publications
2
78
1
1
Order By: Relevance
“…This UroVysion probe mixture consists of centromeric enumeration probes (CEPs) for chromosomes 3, 7, and 17, and a locus-specific indicator (LSI) probe to the 9p21 band that are labeled with red, green, aqua, and gold fluorophores, respectively [12,13]. The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This UroVysion probe mixture consists of centromeric enumeration probes (CEPs) for chromosomes 3, 7, and 17, and a locus-specific indicator (LSI) probe to the 9p21 band that are labeled with red, green, aqua, and gold fluorophores, respectively [12,13]. The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of probes have been investigated to determine which combination yields the highest sensitivity and specificity for TCC detection, the optimal combination was found to combine CEPs for chromosomes 3, 7, and 17, with a LSI probe to the 9p21 band. This combination significantly increased both the sensitivity and specificity of the assay compared with single probe analysis [5,6,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of patients in this multicenter analysis is considerably larger than prior studies. Sarosdy et al [10] identified 36 patients with a negative cystoscopy and a positive FISH assay and compared to 68 patients with a negative cystoscopy and negative FISH assay. With a mean follow-up of 6 months (3-16 months), 15 (41.1 %) patients with a positive FISH were recurred compared to 13 (19.1 %) with a negative FISH (p = 0.014).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is confusion with how to treat patients with a positive urine marker since there is no evidence that performing a biopsy is indicated as would be the case of a patient with a positive cytology yet there is anxiety about the test result. There are several studies that suggest that a patient with a positive FISH is more likely to recur than patients with negative FISH because the test is detecting microscopic disease prior to visualization, a concept referred to as "anticipatory positives" [10,11]. The current studies have been limited by sample size and follow-up duration.…”
Section: Introductionmentioning
confidence: 97%
“…FISH can detect genetic alterations in the urine sediments of patients with urothelial carcinoma. 40,41 UroVysion (Abbott Laboratories, Downers Grove, IL, USA), a multicolored FISH probe set developed to detect bladder cancer, has significantly higher sensitivity than cytology, while maintaining the high specificity of cytology and low sensitivity for Ta tumors. 41,42 FISH also appears to be useful for monitoring the response to intravesical treatment in patients with superficial bladder cancer.…”
Section: Commercially Available Molecular Markersmentioning
confidence: 99%